Changes in the Surface Elevation of the Laohugou Glacier No. 12 in Western Qilian Mountains - Liu, Yushuo; Qin, Dahe; Li, Yanzhao; Qin, Xiang; Li, Zhenlin; Wang, Jing; Jin, Zizhen; Wang, Lihui (Frontiers in Earth Science, 2022)
As the largest valley glacier in the Qilian Mountains, the Laohugou glacier No. 12 (LHG12) has shrunk significantly since 1957. In this study, two topographic maps and a WorldView-2 satellite stereopair image data were used to assess the volume and cumulative mass balance of LHG12 located at the western Qilian Mountains during 1957 - 2015. During the study period, the LHG12 exhibited changes in two processes: slightly ablation and stability in a brief period during 1957–1989 and strong melting and accelerated ablation during 1989–2015. During 1957–2015, the volume of LHG12 decreased by 0.38 km3, the average thickness decreased by 17.23 m, the cumulative mass balance (MB) was -14.69 ± 3.00 m w. e., and ablation was found at glacier-wide. By comparing the previously MB simulation and digital elevation model (DEM) differencing results, it was found that the MB simulation results underestimated the strong melting trend of LHG12 since the 1990s. Temperature rose up, especially in autumn and winter, could cause the ice temperature of LHG12 increase and LHG12 may become more sensitive to the climate change.